Pelatihan pembuatan Herbarium untuk menunjang pembuatan museum Kebun Raya Liwa dan pemberdayaan teknisi di UPTD Kebun Raya Liwa (KRL) Kabupaten Lampung Barat - Yulianty Yulianty; Rochmah Agustrina; Eti Ernawiati; Lili Chrisnawati; Ayu Meilani; Firly Arliandi; Hambali Hambali (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
Indonesia is a country with high plant diversity. One way to get to know the plants is the Botanical Garden. The potential of this botanical garden has not been maximally used as a place to introduce plants for both students and the general public. The involvement of staff at UPTD Kebun Raya Liwa is necessary to collect the observed plants directly and make herbarium to facilitate the introduction of plants in KRL. This herbarium manufacturing training begins with a pre-test to know the ability of krl staff in collecting plants to be made herbarium, followed by the provision of plant herbarium making techniques and field practices. At the end of the training, KRL staff were given a post-test to find out the increased knowledge in making herbarium. The result of this training was an increase in value by 31.54 and the percentage increase in knowledge was 56.94%. The improvement of knowledge and skills for making herbariums in the long term, herbarium can be placed in the KRL Museum.